Features of Speech Reactions to Mental State Concepts - Alekseeva, Ekaterina M.; Gatiyatullina, Galiya M. (Journal of History Culture and Art Research, 2017)
The article is devoted to the problem of mental state associative speech representation. The study involved 31 Russian-speaking subjects (27 females and 4 males) at the age of 18 - 22 years old. The experimental procedure using DMDX program allowed to measure the time of speech response to stimuli - the concepts of 25 mental states. The average reaction time to the concepts of mental states, shown on the computer monitor, made 2114.68 milliseconds. The most rapid associative speech response was the response to the following stimuli: "ecstasy" (1452.54 msec), "meditation" (1569.26 msec), "tranquility" (1685.21 msec), the slowest response is the response to "interest" (2517.5 msec) and "indecision" (2454.63 msec). In total, 448 associations were given to the concepts of 25 mental states by tested subjects - speech reactions, i.e. 17.9 associations per mental state on the average. The greatest number of speech associations (24) was given to the concept of love. The smallest number was given to the concept of ecstasy (11 associations). Associative fields of mental states (meditation, ecstasy, melancholy, tiredness, loneliness) have the most pronounced core. The prospects of the study consist in the performance of a similar associative experiment among the representatives of another culture, as well as in the studying of an estimated and situational associative representation of mental states.